Paraneoplastic Syndrome of Angiomatoid Fibrous Histiocytoma May Be Caused by EWSR1-CREB1 Fusion-induced Excessive Interleukin-6 Production. Issue 7 (October 2015) - Akiyama, Masaharu; Yamaoka, Masayoshi; Mikami-Terao, Yoko; Yokoi, Kentaro; Inoue, Takashi; Hiramatsu, Tomomasa; Ashizuka, Shuichi; Yoshizawa, Jyoji; Katagi, Hiroaki; Ikegami, Masahiro; Ida, Hiroyuki; Nakazawa, Atsuko; et al.
<x xml:space="preserve">Abstract</x> We describe a 7-year-old girl with angiomatoid fibrous histiocytoma (AFH) presenting severe inflammatory symptoms. The cytokine/chemokine profile of serum samples before and after surgery demonstrated that interleukin (IL)-6 had decreased by the greatest percentage. The AFH cells were immunopathologically positive for IL-6 and Tyr705-phosphorylation of signal transducer and activator of transcription 3. The EWSR1-CREB1 fusion gene detected in the tumor leads to continuous activation of CREB1 and IL-6 production, because the promoter region of IL-6 has a CREB binding site. Thus, IL-6 plays pivotal roles in both paraneoplastic syndrome and the oncogenesis of AFH.